Pengembangan Assesmen Pembelajaran PAI pada Lembaga Pendidikan Madrasah dan Pondok Pesantren dalam Era Digital - Siti Masitho; Arman Paramansyah; Sri Yanih; Tri Sumarsih; Neni Yuningsih; Deni Ramdhani (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
This study aims to study the development of PAI learning assessments, as well as the vision, mission and goals, objectives with the concept of planning and evaluation in Madrasah and Islamic Boarding School educational institutions in the digital era.The research method used uses a qualitative approach, through literature studies.Literature Study is carried out by analyzing classical/contemporary literature).The results of the study show that the development of assessments for PAI learning in the digital era is an effort to obtain data/information from learning processes and outcomes to find out how well students, classes/subjects, or certain learning objectives/criteria/achievements are performing based on Islamic teachings in the digital era and the Vision, mission and objectives with the concept of planning and evaluation in educational institutions in madrasas and Islamic boarding schools in the digital era must be adjusted and considered clearly and measurably in order to achieve what is the goal and success of education in madrasas and Islamic boarding schools. Keywords: Assessment Development, Madrasah, Islamic Boarding School, Digital Era.